2018
DOI: 10.1080/10962247.2018.1460634
|View full text |Cite
|
Sign up to set email alerts
|

How best management practices affect emissions in gas turbine power plants—An important factor to consider when strengthening emission standards

Abstract: This study analyzed the potential emission reductions associated with implementing the best management practices (BMPs) on the combined cycle and cogeneration power plants in Beijing. It determined that implementing the BMPs could potentially achieve up to 580 metric tonnes, or 0.6%, reductions of all NOx emissions in Beijing. Many other cities in China and Asia battling air quality issues may find the information useful in order to evaluate the emission reduction potential of their own gas turbine power plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Experiments show that the diagnosis strategy can effectively improve the gas path fault diagnosis efficiency of different gas turbines and effectively solve the problem of low accuracy in gas path control of the gas turbine by improving the cooperative work efficiency [ 19 ]. In summary, in the existing research results, most of the innovations are still focused on the matching analysis of gas turbine type judgment and gas path fault diagnosis, and intelligent analysis algorithms are not applied to many research results [ 20 ]. On the contrary, there are few research studies on the intelligent analysis of data in the process of gas turbine gas path fault diagnosis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments show that the diagnosis strategy can effectively improve the gas path fault diagnosis efficiency of different gas turbines and effectively solve the problem of low accuracy in gas path control of the gas turbine by improving the cooperative work efficiency [ 19 ]. In summary, in the existing research results, most of the innovations are still focused on the matching analysis of gas turbine type judgment and gas path fault diagnosis, and intelligent analysis algorithms are not applied to many research results [ 20 ]. On the contrary, there are few research studies on the intelligent analysis of data in the process of gas turbine gas path fault diagnosis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CCPP models proposed in Figs. 1-2 is developed and adapted based on thoroughly analyzing the literature concepts [92][93][94][95][96][97][98][99][100] relevant to the case study's requirements.…”
Section: Presumptionsmentioning
confidence: 99%
“…[7][8] In the past three decades, the air pollution control strategy in China initially control target level of one pollutant for certain duration through the single-pollutant control. [6][7][8][9] Total suspended particulate, the main focus of the government, has been on acid rain of pollution and acids emissions in the decades of the mid-1980s to the mid-1990s. Later on, it was control focused on the reduction in the 2000s that smog emission as acid rain.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the number of vehicles plying on the roads of Delhi is more than that of the three metropolitan cities of Mumbai, Kolkata, and Chennai taken together and in international threats too. [9,10] There has been no proper technology or methods to treat solid, liquid wastewater, industrial and hospital wastes in the city. Contrary to popular belief, most of the air pollution in Delhi is mainly by uncontrollable vehicular traffic.…”
Section: Introductionmentioning
confidence: 99%